Spendthrift Trusts and Public Policy: Economic and Cognitive Perspectives - Adam J. Hirsch (Washington University Law Quarterly, 1995)
In Part I, I shall explore restraints against voluntary alienation: that is, restrictions on a beneficiary's right to terminate the arrangement-to take the money and run. In Part II, I shall proceed to restraints against involuntary alienation: that is, restrictions on creditors' rights to reach the trust corpus in order to satisfy their claims. Finally, in Part III, I take up the refinement of spendthrift trust doctrine: assuming the expediency of a general warrant to create spendthrift trusts, should lawmakers nonetheless carve out exceptions to their effectiveness?
Keywords: Spendthrift trusts; Government policy; Law & amp; economics